2017
DOI: 10.3171/2016.11.focus16407
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-day readmission and reoperation rates after single-level anterior cervical discectomy and fusion versus those after cervical disc replacement

Abstract: OBJECTIVE The goal of this study was to compare 30-day readmission and reoperation rates after single-level anterior cervical discectomy and fusion (ACDF) versus those after cervical disc replacement (CDR). METHODS The authors used the 2013–2014 American College of Surgeons National Surgical Quality Improvement Program database. Included were adult patients who underwent first-time single-level ACDF or C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 32 publications
2
19
1
Order By: Relevance
“…This may be due to the differing nature of the databases being used. The highest percentage of patients who underwent CDR were between ages 40 to 54 years old and approximately 50% were female, similar to other large database studies [18][19][20]. The most common complication (found in 12.3% of patients) in the first postoperative year after CDR was mechanical and/or bone-related, which included malpositioning of the implant, heterotrophic ossification, and adjacent disc degeneration.…”
Section: Discussionsupporting
confidence: 82%
“…This may be due to the differing nature of the databases being used. The highest percentage of patients who underwent CDR were between ages 40 to 54 years old and approximately 50% were female, similar to other large database studies [18][19][20]. The most common complication (found in 12.3% of patients) in the first postoperative year after CDR was mechanical and/or bone-related, which included malpositioning of the implant, heterotrophic ossification, and adjacent disc degeneration.…”
Section: Discussionsupporting
confidence: 82%
“…When comparing reoperation rates among different types of spinal surgery, studies have found similar 30-day reoperation rates for adult deformity spinal surgery (5%), 47 but lower rates for ACDF (1.2%) and cervical disc arthroplasty (0.4%). 48 Age has been shown to be predictive of a higher risk of reoperation following ACDF. 48 Unplanned reoperation is taxing on a patient’s health and also drives increasing health care costs.…”
Section: Discussionmentioning
confidence: 99%
“… 48 Age has been shown to be predictive of a higher risk of reoperation following ACDF. 48 Unplanned reoperation is taxing on a patient’s health and also drives increasing health care costs. Under the Affordable Care Act, any cost associated with patient readmission up to 30 days following discharge becomes the financial burden of the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23]29 Similarly, Bhashyam et al reported no significant differences with reoperation rates between ACDF and CDA. 30 However, the authors did find a higher readmission rate after ACDF that they attributed to the difference in age groups of each cohort. 30 In contrast, Skeppholmm et al reported higher rates of reoperation after CDA compared to ACDF, likely due to implant migration as both groups had no significant difference in reoperation due to adjacent segment disease.…”
Section: Introductionmentioning
confidence: 91%
“…10,28 In terms of revision and readmission rates, CDA appears to perform similarly, if not better, than ACDF. 17,[21][22][23][24]26,29,30 While some studies have demonstrated decreased rates of reoperation at the adjacent level after CDA, Kelly and colleagues noted no significant difference in secondary surgery when comparing arthroplasty to ACDF up to 5-year follow-up. [21][22][23]29 Similarly, Bhashyam et al reported no significant differences with reoperation rates between ACDF and CDA.…”
Section: Introductionmentioning
confidence: 99%